2015
DOI: 10.1063/1.4930580
|View full text |Cite
|
Sign up to set email alerts
|

High power efficiency distributed oscillator based on composite-right-/left-handed unit cells

Abstract: A microwave oscillator topology based on CRLH (Composite Right-/Left-Handed) unit cells is\ud analyzed theoretically and experimentally tested. The oscillator consists of a CRLH based\ud distributed amplifier and a positive feedback realized by a simple transmission line. The oscillator\ud has two output ports, where the power levels are practically the same. For this topology, we have\ud found the oscillation condition and we demonstrate that each transistor gives the same contribution\ud to the pow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 5 publications
0
12
0
Order By: Relevance
“…A uniform transmission line with characteristic impedance Z 0 and electrical length ϕ is used to realize the FTL component. In [12], it has been demonstrated that for having oscillations, the following condition must be fulfilled:…”
Section: Design Of the Crlh Double Output Distributed Oscillatormentioning
confidence: 99%
See 3 more Smart Citations
“…A uniform transmission line with characteristic impedance Z 0 and electrical length ϕ is used to realize the FTL component. In [12], it has been demonstrated that for having oscillations, the following condition must be fulfilled:…”
Section: Design Of the Crlh Double Output Distributed Oscillatormentioning
confidence: 99%
“…The output ports of the gate and drain lines are loaded by the impedance Z 0 , and FTL is a positive feedback element consisting of a transmission line. In this circuit, each transistor supplies nearly the same amount of power, as demonstrated in [12]. This advantage cannot be obtained by using the conventional low-pass unit cells reported in [6,10,11].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The basic principle of this circuit has been also applied to other components, such as active dividers [5][6][7], frequency doublers [8][9][10], phase shifters [11][12][13][14][15], and oscillators [16][17][18][19][20]. For the latter ones the conventional configuration has been recently modified, replacing the low pass unit cell by a Composite Right-/Left-Handed (CRLH) topology [21,22]. The conceptual configuration of this oscillator is shown in Fig.…”
Section: Introductionmentioning
confidence: 99%